IMPLEMENTASI PANCASILA SEBAGAI PEDOMAN BERETIKA DALAM PERKEMBANGAN IPTEK - Clea Adenta Regina Deeva (Universitas Nias Raya, 2024)
Ethical according to pancasila isa moral implement to humans who do. In this age of digital leisure, meeting the human need for life has been greatly influenced by the technological developments. Increasingly progressive scientific developments made major changes in the lives of everyone, including Indonesian youths. Rapid technology continues to flourish must follow the established pancasila ground rules. Pancasila became the basis for IP development in Indonesia because each pancasila value is important and shows ethics in the development of iptek. Vast Numbers of youth do not implement the pancasila value principle. Pancasila is good and consistent if the implementation of pancasila value in ethical terms is well understood and based on technological development. The implementation of pancasila value needs to be a consciousness for young people to hold firm principles and determination and based on consistent